(untitled) (The Research of Medical Science Review, 2025)
Objective: To provide insights into hemodynamic changes associated with using Saddle block vs Spinal anesthesia in patients undergoing Trans-ureteral resection of prostate. Methodology: This randomized control trail, conducted at the Bahria international hospital, phase 8, Rawalpindi, investigated the hemodynamic stability of patient when using saddle anesthesia block vs spinal anesthesia. Demographic variables, prostatic size, and co-morbid were recorded. Hemodynamic instability was described using a cutoff of Mean arterial Pressure and Heart rate change of 20%, and hemodynamic status was assessed via an automated Non-invasive cardiac monitor. Statistical analysis was done using IBM SPSS Statistics,Version 27. Results: The study included 60 participants divided into two groups formed by non-probability consecutive sampling and receiving either spinal or saddle block indicated as group A or B, respectively. Heart Rate showed significant reduction in Group B’s HR(M = 73.5, SD = 6.1, p < 0.001) suggests improved hemodynamic stability while Higher MAP in Group B(M = 73.5, SD = 5.1 ,p =0.006) indicates better perfusion pressure. Level of Block in Group B’s higher scores (p < 0.001) imply a more effective block. Conclusion: Our study confirms significant differences in hemodynamic parameters between spinal and saddle anesthesia during TURP procedures. Saddle Anesthesia exhibited a significantly lower heart rate (M = 73.5, SD = 6.1) compared to Spinal (M = 81.3, SD = 7.2), Additionally, Saddle block had a higher mean arterial pressure (M = 73.5, SD = 5.1) than spinal (M = 70.1, SD = 4.2). This indicates Saddle block group experienced more stable hemodynamic profiles, which may translate to better perioperative outcomes, especially for patients with increasing age and cardiovascular comorbidities. Our results underscore the importance of saddle anesthetic in managing hemodynamic stability during TURP as the general population is elderly individuals (mean age 65.2 ± 4.3) with a greater susceptibility for hemodynamic derangements.